Sicherheit als Grundsatz : eine grundrechtsdogmatische Rekonstruktion im Unionsrecht am Beispiel der Cybersicherheit - Leuschner, Sebastian (Internet und Gesellschaft, 2017)
In its basic rights doctrine, security takes on various different guises. However, the understandings of security as a legitimate aim, as a positive obligation to protect, or even as a fundamental right, do not do justice to its special need to be treated differently. How, then, might security be fundamentally re-thought?